Financial Feasibility of Coconut Shell Briquette Manufacturing for Export-Oriented Biomass Industries - Ana Noor Maulana (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2025)
The increasing global demand for renewable and environmentally friendly fuels has positioned coconut shell briquettes as a competitive biomass-based energy product, particularly for export markets. This study evaluates the financial feasibility of establishing a coconut shell briquette manufacturing plant in Indonesia by integrating systematic facility planning with comprehensive investment appraisal. A quantitative approach was employed, combining capital investment estimation, operating cost analysis, profit and loss projections, balance sheet evaluation, and capital budgeting techniques over a ten-year planning horizon. Financial feasibility was assessed using key indicators, including Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit–Cost Ratio (BCR). The results indicate that the proposed project is economically viable, achieving a payback period of approximately 2 years and 7 months, a positive NPV at a 10% discount rate, and an IRR exceeding the minimum attractive rate of return. The financial projections demonstrate stable cash flows, prudent liability management, and sustained equity growth, reflecting strong investment performance and resilience. In addition, the integration of systematic layout planning supports efficient material flow and cost optimization, enhancing overall operational feasibility. The findings confirm that coconut shell briquette manufacturing represents a financially attractive and sustainable investment opportunity, contributing to biomass valorization, export competitiveness, and renewable energy development. This study provides practical insights for investors, industry practitioners, and policymakers in evaluating and developing export-oriented biomass manufacturing projects.